The Evolution of Thai Aromatic Art: The Aesthetics of Cultural Wisdom - Amparot, Hattapon (Journal of Cultural Approach, 2024)
Thai aromatics are considered beautiful Thai art. Thai aromatics are classified as aesthetics related to Thai art, culture, and wisdom (Deesawad & Krutasean, 2022). They have been associated with people since ancient times (Kengcharoen, 2009). The study found that Thai incense has an interesting historical origin and evolution, which can explain the importance of aesthetics arising from historical events from four important eras: Sukhothai, Thonburi, Ayutthaya, Rattanakosin, and Thai aromatics. There are a variety of herbs mixed together artfully to create a fragrant scent and aromatherapy properties. It is considered high art. The smells are based on medical or scientific principles, which blend principles of social science and Thai culture. Therefore, it can be concluded that Thai incense is an aesthetic that is delicate, profound, and has value related to culture and beliefs. Perception occurs through the senses, resulting in happiness through the aesthetic experience.